Strategies to manage the risks faced by consumers in developing e-commerce - Kiran Javaria; Omar Masood; Fernando Garcia (Insights into Regional Development)
The study investigates the management of risk in E- Commerce and what different barriers are faced by consumers during an uncertain and risky situation. The study utilizes both primary and secondary data in order to get reliable results. There are different risk factors that affect the purchasing behaviour of consumers who shop online. The consumer’s perception of risk may be the result of all the emotional processes through which consumers recognize, organize and provide meaning to sensations received, such as the need for product quality, safety online and overall satisfaction. The primary data consists of a survey of online shoppers. The research data and questionnaire was administered to 972 internet users who are classed as experienced and avid users. The secondary data includes an analysis of the various theories of consumer behaviour, models of online adoption, risk factors to marketing and shopping online, models of the adoption of innovation and new ways of marketing and trade. Both techniques are utilized that would examine the relationship between perceived risk strategies and customer satisfaction as well as examined the customer involvement and propensity to take risk on existing relation of online shopping.